2006
DOI: 10.1002/path.2084
|View full text |Cite
|
Sign up to set email alerts
|

The C allele of the GNB3 C825T polymorphism of the G protein β3‐subunit is associated with an increased risk for the development of oncocytic thyroid tumours

Abstract: Carriers of the C allele of the common C825T polymorphism in the GNB3 gene of the G protein have been associated with the development of follicular thyroid adenomas. Since the C allele of this polymorphism is related to a lower signalling capacity, it was speculated whether the C825T polymorphism may play a particular role in oncocytic thyroid tumours, which are recognized for their reduced ability to synthesize thyroid-specific proteins and hormones, although they possess an intact thyroid-stimulating hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…This polymorphism has been associated with oncogenesis and increased metastases in a variety of cancers, including breast, colorectal, head and neck squamous cell, and thyroid cancers. [19][20][21][22][23] The results of these studies, combined with our data showing a mutation in malignant melanoma in GNB3, suggest that further examination of pathway is warranted.…”
mentioning
confidence: 70%
“…This polymorphism has been associated with oncogenesis and increased metastases in a variety of cancers, including breast, colorectal, head and neck squamous cell, and thyroid cancers. [19][20][21][22][23] The results of these studies, combined with our data showing a mutation in malignant melanoma in GNB3, suggest that further examination of pathway is warranted.…”
mentioning
confidence: 70%
“…The modulatory eVects upon G protein-mediated signal transduction pathways have been associated with various clinically important disorders (SiVert 1996a, b;SiVert 1998). Recently, genotypes of the C825T polymorphism in GNB3 were shown to be associated with the prognosis of diVerent malignancies, such as bladder cancer, bone metastasis in breast cancer, and diVerentiated thyroid carcinomas of follicular cell origin (Clar et al 2008;Eisenhardt et al 2005;Sheu et al 2005Sheu et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…The GNB3 825T-allele has been associated with enhanced signal transduction and the occurrence of an alternative splice variant referred to as G 3s (SiVert 1998(SiVert , 2003SiVert et al 2000). Genotypes of this polymorphism have been shown to be associated with the prognosis of diVerent malignomas, such as bladder cancer, bone metastasis in breast cancer, diVerentiated thyroid carcinomas of follicular cell origin and head and neck squamous cell carcinoma, respectively (Clar et al 2008;Eisenhardt et al 2005;Lehnerdt et al 2008;Sheu et al 2007). Thus, we investigated a potential association of genotypes of the GNB3 C825T polymorphism as a possible parameter for survival in patients with GBM.…”
mentioning
confidence: 98%
“…This study revealed a shorter time for metastasis in 825T-allele carriers compared to individuals that were homozygous for the GNB3 825C allele. In subsequent studies, it was found that individuals who were suffering from either oncocytic thyroid tumours, head and neck squamous cell carcinoma or bladder carcinoma, were at a significantly higher risk for tumour relapse and death when they were homozygous for the GNB3 825T allele [20,21]. On the contrary, a different study found that the GNB3 825T allele appears to be protective against the development of bone metastasis in breast cancer patients when compared to individuals homozygous for the 825C allele [22].…”
Section: Introductionmentioning
confidence: 99%